Effects of curcumin gel on osteoclastogenic bone markers in experimental periodontitis and alveolar bone loss in wistar rats - Sha, Aram Mohammed (J Dent Sci, 2021)
BACKGROUND/PURPOSE: Curcumin has anti-inflammatory impacts and was suggested as an inflammatory disease therapy. This study aimed to investigate the implications of curcumin gel on experimental periodontitis (EPD) and alveolar bone loss in rats. MATERIALS AND METHODS: In this study, twenty-four male Wistar rats were divided equally into four groups: negative control (with no EPD); positive control (EPD induced around lower centrals without treatment); control-treated group: EPD treated with chlorhexidine; and test EPD group treated with curcumin. After 30 days, the serum concentrations of RANKL and IL-1β were measured via ELISA. All animals were sacrificed, and mandibular central incisors with the periodontium were removed. The lingual probing depth and radiographical alveolar bone loss were measured, then samples processed for routine preparation of H&E stained sections and histologically assessed for counting inflammatory cells, osteoclasts, and PDL width. RESULTS: A significant decrease in the inflammatory cells infiltration, probing depth, and osteoclast numbers with the improvement of PDL associated with a reduction in RANKL and IL-1β serum concentration were seen in both EPD treated groups. CONCLUSION: Curcumin is as effective as chlorhexidine in treating experimental periodontitis in rats. It was demonstrated to stop bone destruction related to periodontitis by regulating the RANKL and IL-1β markers level in the blood.